Development of aerA Gene-Based PCR Primers as DNA Biomarkers for the Molecular Detection of Aeromonas hydrophila Using an In Silico Approach - Septianto Wikan Nurhidayat; Naina Nur Prastiti (Punggawa Legacy Center, 2026)
Aeromonas hydrophila is one of the major bacterial pathogens affecting cultured fish, causing Motile Aeromonas Septicemia (MAS) and substantial economic losses in aquaculture. Early detection of this pathogen is essential for effective disease prevention and control. This study aimed to design a primer pair targeting the aerA virulence gene as a DNA biomarker for the molecular detection of A. hydrophila using an in silico approach. The aerA gene sequence (GenBank accession number EU254217.1) was retrieved from the NCBI database and used as the template for primer design using Primer3Plus. The designed primers were evaluated based on primer length, melting temperature (Tm), GC content, predicted amplicon size, and the potential formation of secondary structures. Primer specificity was subsequently assessed using In Silico PCR against several Aeromonas genomes. The selected primer pair consisted of the forward primer 5'-GAGAAGACGGCCATCAAGGT-3' and the reverse primer 5'-TGTGGTTCCAGTTCGGGC-3', producing a predicted amplicon of 529 bp. The primers exhibited melting temperatures of 59.7°C and 59.9°C with GC contents of 55.0% and 61.1%, respectively, indicating suitable characteristics for PCR amplification. In Silico PCR analysis demonstrated successful amplification exclusively in A. hydrophila genomes, while no amplification was detected in the non-target Aeromonas species evaluated. These findings suggest that the aerA gene is a promising DNA biomarker for the molecular detection of A. hydrophila . However, further in vitro validation is required to confirm the sensitivity and specificity of the designed primers using field isolates.